1995
DOI: 10.1002/jcp.1041650121
|View full text |Cite
|
Sign up to set email alerts
|

Changes in membrane potential during the progression of MCF‐7 human mammary tumor cells through the cell cycle

Abstract: We previously reported that MCF-7 cells were arrested in the G0/G1 phase of the cell cycle by agents known to block the activity of ATP-sensitive potassium channels (Woodfork et al., 1995, J. Cell Physiol. 162:163-171). The goal of our current study was to determine if MCF-7 cells undergo changes in membrane potential during the cell cycle that might be linked to changes in K permeability. The resting membrane potentials of unsynchronized MCF-7 cells during exponential growth phase were measured using sharp gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
107
0
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 139 publications
(115 citation statements)
references
References 19 publications
7
107
0
1
Order By: Relevance
“…Inhibition of K þ channels leads to membrane depolarization and cellcycle arrest in early G 1 phase in the MCF-7 human breast carcinoma cell line (Wang et al, 1998). Conversely, activation of K þ channels promotes the cellcycle progression from the G 0 /G 1 to S phase (Wonderlin et al, 1995;Ouadid-Ahidouch et al, 2001;Chittajallu et al, 2002). Here, we demonstrated that the activity of IKCa1 channels contributed to the progression of EC cells through the G 1 phase in the G 1 /S transition.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of K þ channels leads to membrane depolarization and cellcycle arrest in early G 1 phase in the MCF-7 human breast carcinoma cell line (Wang et al, 1998). Conversely, activation of K þ channels promotes the cellcycle progression from the G 0 /G 1 to S phase (Wonderlin et al, 1995;Ouadid-Ahidouch et al, 2001;Chittajallu et al, 2002). Here, we demonstrated that the activity of IKCa1 channels contributed to the progression of EC cells through the G 1 phase in the G 1 /S transition.…”
Section: Discussionmentioning
confidence: 99%
“…30). To determine whether this difference results from membrane polarization that may be induced by current flowing between the intracellular nanoprobe and the external reference electrode, we measured the dependence of ⌬E 1/2 on concentration (c FcCH 2 OH ).…”
Section: Secm Measurements and Intracellular Voltammetrymentioning
confidence: 99%
“…Although the membrane potential of cancer cells tends to be more depolarized, cell cycle phase-specific changes in membrane potential have been reported. MCF-7 human mammary cells display a transient hyperpolarization at G1-S transition, which was suggested to be a result of an increase in membrane permeability to potassium (Wonderlin et al, 1995;Fig. 2).…”
Section: Potassium Channel In Proliferation and Tumor Growthmentioning
confidence: 99%